Effects of micronutrients on seed yield and oil content of Brassica napus L. cv. Talayeh (Bangladesh Journal of Botany, 2015)
Foliar application of micronutrients like iron, zinc and manganese significantly increased 1000-kernel weight, grain yield, oil content of seed and harvest index of Brassica napus L. cv. Talayeh. Changes in grain yield was primarily due to the number of pod per plant and that of oil yield was due to grain yield. In general, applying two parts per thousand of the micronutrient was the best treatment to obtain high qualitative and quantitative yield in cv. Talayeh in this region. DOI: http://dx.doi.org/10.3329/bjb.v43i2.21679 Bangladesh J. Bot. 43(2): 231-233, 2014 (September)